2021
DOI: 10.1159/000517883
|View full text |Cite
|
Sign up to set email alerts
|

Can Urinary KIM-1 and NGAL Predict Management Endoscopic Surgery in Acute Unilateral Obstructive Stone Disease? Results from a Prospective Cohort Study

Abstract: <b><i>Introduction:</i></b> Kidney injury molecule-1 (KIM-1) and neutrophil gelatinase-associated lipocalin (NGAL) are the leading novel biomarkers used efficiently in acute kidney injury (AKI). The levels of these biomarkers increase especially in the early period of nephrotoxic and ischemic renal damage. In this study, we aimed to investigate the clinical importance of NGAL and KIM-1 biomarkers used in the effective evaluation of kidney functions in patients with acute unilateral obst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…This could be attributed to the stone clearance and/or use of NSAIDs, which might have had a favourable impact on the inflammatory process and their associated biomarkers. Similar results for urinary KIM-1/Cr and urinary NGAL/Cr ratios were recorded after ureteroscopy [18].…”
Section: Discussionsupporting
confidence: 82%
“…This could be attributed to the stone clearance and/or use of NSAIDs, which might have had a favourable impact on the inflammatory process and their associated biomarkers. Similar results for urinary KIM-1/Cr and urinary NGAL/Cr ratios were recorded after ureteroscopy [18].…”
Section: Discussionsupporting
confidence: 82%
“…The levels of these biomarkers increase, especially in the early period of nephrotoxic and ischemic renal damage [7,8]. Several studies have shown that the levels of AKI biomarkers can increase after urinary system stone treatments [9][10][11]. In this study, our aim was to investigate the effect of the diameter of UAS used during RIRS on renal injury through the evaluation of AKI biomarkers.…”
Section: Introductionmentioning
confidence: 99%